PENGARUH SERVICE QUALITY DAN FACILITIES TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA ALAS VEENUZ TRAWAS - Putri Dhea Lusanti; Woro Utari; Sri Suprapti (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
The background of this study is driven by a phenomenon occurring at Alas Veenuz Trawas, where issues regarding customer loyalty are presumed to be closely related to the inconsistent aspects of service quality. Consequently, the research problem formulated in this study is